Early versus Late Tracheostomy Promotes Weaning in Intensive Care Unit Patients: a retrospective observational study: Early versus Late Tracheostomy - Marinaki, Chrisoula; Kapadochos , Theodoros; Katsoulas , Theodoros; Rubbi , Ivan; Liveri , Athanasia; Stavropoulou , Areti; Bonacaro, Antonio; Papageorgiou , Dimitrios (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The time interval between the patients’ intubation and the performance of a tracheostomy has been considered as critical for the disease prognosis and outcome. The aim of the present study was to compare and contrast the outcomes of early vs late tracheostomy with regard to ICU patients’ weaning from respiratory support.Methods: This retrospective observational study, involved patients who were hospitalized in two general and one Covid-19 ICUs of two tertiary hospitals in Athens and were subjected to tracheostomy. Data were collected from the patients’ medical records in order to estimate the duration of patient weaning and the number of days from the patients’ intubation until the time of tracheostomy. In the present study the term earlytracheostomy denotes tracheostomy performed within 14 days from patient intubation and late tracheostomydefines the tracheostomy carried out after 14 days. For Covid-19 patients, guidelines suggested that tracheostomies should be performed 21 days following intubation, due to the high risk of virus transmission.Results: One hundred and thirty-one patients who underwent tracheostomy participated in the study. Most tracheostomies were performed using the percutaneous technique. The group of patients tracheostomized within 14 days after their admission in ICU weaned faster from respiratory support compared to ones who were tracheostomized after 14 days.Conclusions: The most common distinction between early and late tracheostomy is 14 days, with early tracheostomy being more beneficial in terms of patients’ outcomes, and specifically ICU patients’ weaning.